Spanish seamen (circular) - Tewson, Vincent
C01-0008-001 Telegraphic Address: TRADUNIC, SOWEST, LONDON. Telephone: VICTORIA 9020 TRADES UNION CONGRESS GENERAL SECRETARY SIR WALTER CITRINE, K.B.E. TO WHOM ALL COMMUNICATIONS SHOULD BE ADDRESSED. TRANSPORT HOUSE, SMITH SQUARE, LONDON, S.W.1. Department International Our Ref. HVT/AC/56 Your Ref. 5th December, 1939. SPANISH SEAMEN. As has been anticipated for some time, regulations have now been issued by the Government with regard to the employment of friendly aliens, as a result of which the Spanish seamen on our funds will be permitted to accept employment in the U.K., subject to certain conditions. The procedure will be that prospective employers will apply to the local Employment Exchange for permission to employ an individual refugee in a post for which no British labour is available, and the local Exchange, after consultation with the Ministry of Labour in London, will endorse the refugee's certificate of registration for the post in question. You will observe from the attached statement, made in the House by the Home Secretary, that regard will be paid to the views of the Unions concerned. Probably, therefore, you would see what opportunities there are for employment, and if any vacancy occurs, consult immediately the appropriate Trade Union locally, to ensure that no difficulty would arise if the employment were taken. In the new circumstances, you may be able to help the seamen and, of course, relieve our own heavy responsibilities. Yours sincerely, H. . TEWSON. Assistant Secretary. Copy statement. 292C/946/1/8